Risktaking Behavior in Fintech Users Peer To Peer Lending (Journal of Social and Industrial Psychology, 2023)
Current technological developments provide convenience to the community, one of which is in debt through online loan applications. However, this has led to a change in the behavior of people who like to make loans without thinking about the risks involved. This study aims to describe risk-taking behavior in peer-to-peer lending fintech users. This type of research uses descriptive quantitative methods. The sample used in this study amounted to 160 subjects of peer-to-peer lending fintech users. Accidental sampling techniques were used in this study. The method used is a descriptive analysis method and data collection using a risktaking behavior scale with a reliability coefficient value of 0.923 with a total item of 25 and is declared valid in each variable. Based on analysis through research data software tools on the description of risktaking behavior in peer-to-peer lending / p2p fintech users, it was concluded that peer-to-peer lending / p2p fintech users were in the low risktaking behavior category of 60.6%, medium criteria of 35%, and high criteria of 4.4%. This means that the risk-taking behavior raised by the subjects of peer-to-peer lending fintech users in this study is quite low whereas behavior that contains risk leads individuals to the negative possibility they will receive is low.